PENERAPAN CHUNKING STRATEGY UNTUK MENINGKATKAN KEMAMPUAN MEMAHAMI TEKS BAHASA INGGRIS PADA MAHASISWA STKIP PESISIR SELATAN - Antoni Jamin; Tiara Indah Sari; Titik Hardewi Yani; Efendi Efendi; Sefrinal Sefrinal; Okviani Syafti; Ramadhani Ramadhani (Jurnal Manajemen Pendidikan, 2026)
During the learning process, students often appear uninterested when required to read texts. This is influenced by several factors, including lecturers failing to tailor teaching methods or strategies to students' needs, the presentation of lengthy reading materials, and students' limited vocabulary, which affects their comprehension. This study aims to improve the ability to understand texts in STKIP Pesisir Selatan for english students by implementing a chunking strategy. This research is a class action research conducted in campus STKIP Pesisir Selatan in June 2026 with a total of 28 students as research subjects. Based on the results of this classroom action research, it can be concluded that the application of learning by implementing a chunking strategy has succeeded in increasing the learning outcomes of English students of STKIP Pesisir Selatan in improving the ability to understand English texts. This can be seen from the increase in the number of students who have achieved the learning outcomes of 15 students (53.57%) in cycle I increasing to 21 students (75%) in cycle II. This increase is in line with the increase in lecturers performance. In cycle I the average score of lecturers performance was 21.67 or 72.22% of the ideal score increasing to 25.33 or 84.44% in cycle II.